ANALISIS KINERJA KEUANGAN PERUSAHAAN DITINJAU DARI RENTABILITAS, LIKUIDITAS DAN SOLVABILITAS (STUDI KASUS PADA PT. RIKA MART BAUBAU): (Analysis of Financial Performance Assessed from Profitability, Liquidity and Solvability Case Study at PT. Rika Mart Baubau) - Abdullah, Rudi (Uniqbu Journal of Social Sciences, 2020)
This reasearc aimed to analyze financial performance. Rika Mart Baubau years 2018 - 2019 in terms of profitability, liquidity and solvency. Data was collected through interviews and documentation. Analysis of data using qualitative descriptive analysis. The results showed that the company's liquidity during the last two years shows an increase in Cash Ratio of 16:32%. The increase in current assets due to the addition of cash and bank in the year 2019, while the Current Ratio and Quick Ratio companies decreased respectively by 12.72% for the Current Ratio and Quick Ratio 8.89% for. This occurs because of the increase occurred Passiva smoothly that additional debt from PT. Rika Mart. In general liquidity ratio current ratio, quick ratio and cash ratio is below 200% in 2019 and 2018 so it is still relatively very low and illiquid (ilikuid). Solvency Ratio Companies for 2019 and 2018 is still quite solvable, still showing a good situation for the company, but remain aware of and need for additional capital to improve the company's financial performance is better in the future. In 2019, Gross Margin Ratio increased by 4:57% This shows the cost savings incurred to get production can be achieved. As for the Operating Margin Ratio decreased by 0.98%. Keywords: Liquidity, Solvency and Profitability